Evolution, Ecology, and Zoonotic Transmission of Betacoronaviruses: A Review - Herbert F. Jelinek; Herbert F. Jelinek; Herbert F. Jelinek; Mira Mousa; Eman Alefishat; Eman Alefishat; Eman Alefishat; Wael Osman; Ian Spence; Dengpan Bu; Samuel F. Feng; Samuel F. Feng; et al. (Frontiers in Veterinary Science, 2021)
Coronavirus infections have been a part of the animal kingdom for millennia. The difference emerging in the twenty-first century is that a greater number of novel coronaviruses are being discovered primarily due to more advanced technology and that a greater number can be transmitted to humans, either directly or via an intermediate host. This has a range of effects from annual infections that are mild to full-blown pandemics. This review compares the zoonotic potential and relationship between MERS, SARS-CoV, and SARS-CoV-2. The role of bats as possible host species and possible intermediate hosts including pangolins, civets, mink, birds, and other mammals are discussed with reference to mutations of the viral genome affecting zoonosis. Ecological, social, cultural, and environmental factors that may play a role in zoonotic transmission are considered with reference to SARS-CoV, MERS, and SARS-CoV-2 and possible future zoonotic events.